Implementasi Pemberian Izin Terhadap Pelaku Usaha Kecil Melalui Kebijakan Online Single Submission (OSS) Perspektif Fiqih Siyasah Idariyah - Devi Herlina; Imam Mahdi; Qolbi Khairi (CV. Doki Course and Training, 2024)
The purpose of this study is to determine the Implementation of Granting Permits to Business Actors Through the Online Single Submission (OSS) Policy from the Fiqh Siyasah Perspective, What are the Constraints and Obstacles and Supporting Factors for Granting Permits to Business Actors Through the Online Single Submission (OSS) Policy from the Fiqh Siyasah Perspective, What is the Review from Fiqh Siyasah on the Implementation of Granting Permits to Business Actors Through the Online Single Submission (OSS) Policy from the Fiqh Siyasah Perspective. This study uses an Empirical Juridical approach method. Data collection methods use interviews and observations. Data analysis techniques use descriptive analysis. The results of this study are: Limited Digital Infrastructure: OSS implementation is hampered by inadequate digital infrastructure, such as slow or unstable internet connections in a number of areas, reducing accessibility and efficiency of system use. Human Resources: There are still many people and business actors, especially in Seluma, who do not understand the optimal use of OSS, resulting in difficulties in obtaining permits through the system. Siyasah Fiqh Perspective: The implementation of granting permits through OSS is analyzed based on the principles of siyasah fiqh, including Maqasid al-Shariah, Maslahah, justice, ease of access, protection of individual rights, and compliance with the law.